MÜZİK EĞİTİMİNDE VİYOLONSEL ALANINA YÖNELİK YAPILAN ÇALIŞMALARIN İNCELENMESİ - Türkmen, Hüseyin; Özcan Coşkunsoy, Bilgen (TURAN : stratejik arastirmalar merkezi, 2025)
This research aims to examine the graduate studies on the cello instrument within the scope of vocational music education. The research study group comprises 64 graduate theses completed in higher education institutions operating in music education between 2017 and 2022 in Türkiye. The relevant data were accessed using the thesis archive link on the Council of Higher Education website. The research is a qualitative study, and the document review method was used to analyze the data. Master's and doctoral theses were examined and classified according to university, year, and subject titles, and frequency distributions were made. The results obtained are presented in relevant tables. In line with the findings of the research, it was concluded that the master's theses in the field of Cello were primarily conducted at Gazi University, the number of master's thesis studies in this field was higher in 2019, and the master's theses in the field of Cello were focused on issues related to vocational music education.